PEMBERITAAN ROHINGYA PADA PORTAL BERITA BBC NEWS (KAJIAN ANALISIS WACANA KRITIS) - Yusuf, Yogi Muhammad; Asri Fitrananda, Charisma (Linimasa : Jurnal Ilmu Komunikasi, 2021)
Abstrak This article aims to explain how BBC News Indonesia describes cases of hoax reporting related to hatred carried out and the expulsion of Rohingya refugees in the Aceh region of Indonesia, using a critical paradigm discourse analysis approach (Critical Discourse Analysis) modeled by van Dijk. The Rohingya ethnic group itself is an ethnic minority who are Muslim and of course the massacre of this ethnic group has sparked criticism from various parts of the world, including Indonesia, which is predominantly Muslim. The news about the Rohingya case has become confusing and there is a lot of hoax reporting in various media in Indonesia, one of which is media anonymously, issues and news like this can influence readers to believe the news. According to Can Dijk (2004), there are two main discursive strategies in reporting on an individual/group in the media, and these strategies are related to "THEM". The us vs them labeling is realized through several discourse strategies, including: the strategy of submitting authoritative arguments, the strategy of using passive sentences and the number game strategy. Several discourse strategies are used by the media - in this case BBC News Indonesia - to give positive labels (positive self-presentation) or (negative other-presentation) to the individuals/groups being reported on.